Pengaruh Harga, Kualitas Pelayanan dan Cita Rasa Terhadap Kepuasan Pelanggan Kedai Kopi Momen Klasik - Rahmah, Muthiatur; Winarno, Sri Tjondro; Wijayati, Prasmita Dian (Universitas Nahdlatul Ulama Blitar, 2026)
Customer satisfaction is a very important aspect and needs to be considered in coffee shops in order to compete. The influence of price is thought to be one of the determining factors of customer satisfaction with the products provided. The quality of service provided by the coffee shop to consumers also affects customer satisfaction. Another thing related to customer satisfaction is taste. The goal that the author wants to achieve is to determine the effect of price, service quality, and taste on customer satisfaction using the SEM-PLS method with a sample of customers at the ‘’Momen Klasik’’ coffee shop. The collection of research data used a questionnaire given to customers and obtained a sample of 50 respondents. The results show that the price variable has a positive and significant effect on customer satisfaction at the ‘’Momen Klasik’’ coffee shop with a p-value significance of 0.027. The service quality variable has a positive and significant effect on customer satisfaction at the classic moment coffee shop with a p-value significance of 0.013. The taste variable has a positive and significant effect on customer satisfaction at the ‘’Momen Klasik’’ coffee shop with a p-value significance of <0.001.